Biology and behaviour of the neotropical ant-mimicking spider Aphantochilus rogersi (Araneae: Aphantochilidae): nesting, maternal care and ontogeny of ant-hunting techniques - Castanho, L. M.; Oliveira, P. S. (Oxford University Press, 1997)
Aphantochilus rogersi is an ant-mimicking spider that preys exclusively on cephalotine ants. The spiders oviposit in close proximity to nests of the model ant Zacryptocerus pusillus, and emergent spiderlings tend to remain in the vicinity of natal egg sacs. Females of A. rogersi actively defend their egg sacs against approaching workers of Z. pusillus, but the latter may sometimes destroy the eggs. Feeding specialization on these ants is confirmed by more than 300 observations of young and adult A. rogersi carrying ant corpses in the held. Although A. rogersi possesses several behavioural traits which may reduce the risk of being injured by ants during subjugation, field and laboratory observations showed that social defence by Z. pusillus may cause mutilation to the spiders. Tests in captivity revealed an ontogenetic change in the prey-capture techniques employed by A. rogersi. Early-instar spiderlings can apparently only seize the ant's petiole tightly if they are able to approach the ant from the front. As the ant is paralysed, the spiderling positions itself vertically in relation to the substratum. Larger spiders, on the other hand, attack ants most frequently from behind, and seem better equipped to seize the ant's petiole firmly with their larger chelicerae. Owing to their greater strength, late-instar spiders are able to Lift the struggling ant aloft. The selection of a suitable oviposition site, the mother's ability to defend herself and the eggs from nearby ants, and the capacity to capture and subdue ants safely from emergence to maturity, are regarded as crucial traits inherent in the mimetic and feeding specialization by A. rogersi.